Psychiatric hospital reform in low-income and middle-income countries Structured Individualised inTervention And Recovery (SITAR): a two-arm pragmatic randomised controlled trial study protocol. Issue 5 (5th May 2020) - Raja, Tasneem; Tuomainen, Helena; Madan, Jason; Mistry, Dipesh; Jain, Sanjeev; Singh, Swaran
Abstract : Introduction: Low-income and middle-income settings like India have large treatment gaps in mental healthcare. People with severe mental disorders face impediments to their clinical and functional recovery, and have large unmet needs. The infrastructure and standards of care are poor in colonial period psychiatric hospitals, with no clear pathways to discharge and successfully integrate recovered individuals into the community. Our aim is to study the impact of psychiatric hospital reform on individual patient outcomes in a psychiatric hospital in India. Methods and analysis: Structured Individualised inTervention And Recovery (SITAR) is a two-arm pragmatic randomised controlled trial, focusing on patients aged 18–60 years with a hospital stay of 12–120 months and a primary diagnosis of psychosis. It tests the effectiveness of structural and process reform with and without an individually tailored recovery plan on patient outcomes of disability (primary outcome WHO Disability Assessment Scale), symptom severity, social and occupational functioning and quality of life. A computer-generated permuted block randomisation schedule will allocate recruited subjects to the two study arms. We aim to recruit 100 people into each trial arm. Baseline and outcome measures will be undertaken by trained researchers independent to the case managers providing the individual intervention. A health economic analysis will determine the costing of implementing the individually tailored recovery plan. Ethics and dissemination: The study will provide answers to important questions around the nature and process of reforms in institutional care that promote recovery while being cognizant of protecting human rights, and dignity. Ethical approval for SITAR was obtained from a registered ethics committee in India (Institutional Ethics Committee VikasAnvesh Foundation, VAF/2018-19/012 dated 6 December 2018) and the University of Warwick's Biomedical and Scientific Research Ethics Committee (REGO-2019–2332, dated 21 March 2019), and registered on the Central Trial Registry of India (CTRI/2019/01/017267). Trial results will be published in accordance to CONSORT guidelines.